Effect of Organic Enrichment and Desalination on Sample Pretreatment for Non-targeted Analysis of Dissolved Organic Matter in Urban River Water by LC-ESI-Orbitrap MS - Kasuga, Ikuro; Furumai, Hiroaki; Kurisu, Futoshi; Uehara, Yutaro (Journal of Water and Environment Technology, 2025)
High-performance liquid chromatography/high-resolution mass spectrometry (LC/HRMS) can be used to perform non-targeted analysis of dissolved organic matter (DOM) in environmental water at the molecular level without specifying target analytes prior to measurement. Pretreatment of samples subjected to LC/HRMS strongly affects the comprehensiveness of the analysis. In this study, the use of freeze-drying, vacuum vortex evaporation, and solid-phase extraction (SPE) for sample pretreatment was investigated as well as direct injection of untreated samples. Organic recovery, anion removal, and detected components were evaluated for Japanese urban river water with a high content of sewage effluent. Among the investigated techniques, SPE effectively removed anions and yielded the largest number of detected DOM components. Using the other three methods resulted in higher recoveries of organic matter than SPE but left residual inorganic ions that inhibited detection. Thus, SPE was determined to be the best single method for non-targeted screening analysis. Considering that some components were only detected using pretreatment methods other than SPE, it is recommended that SPE be combined with other methods to improve the comprehensiveness of the analysis.